2011
DOI: 10.1007/s11746-011-1990-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Chia (Salvia hispanica L.) Seed Oil: Effect of Antioxidants and Storage Conditions

Abstract: The oxidative stability of chia oil was evaluated by measuring the effectiveness of the addition of rosemary (ROS) and green tea (GT) extracts, tocopherols (TOC), ascorbyl palmitate (AP) and their blends, and studying the influence of storage conditions. The addition of antioxidants increased induction time, depending on their type and concentration. Considering antioxidants individually, AP at 5,000 ppm was the most effective, whereas ROS ? GT at 2,500 and 5,000 ppm provided the best protection among the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
65
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 23 publications
20
65
1
8
Order By: Relevance
“…Grampone et al (2013) reported an oxidation temperature of 176°C using pure oxygen as oxidizing atmosphere at a higher rate.This could explain the diff erence, along with discrepancies in oil composition, as the omega-6 concentration is not reported by the authors. The same may be concluded when comparing to the results from Ixtaina et al (2012), who reported an oxidation temperature of (168.2 ± 2.8)°C. DSC thermograms demonstrated that the encapsulation of chia oil increased its oxidative stability since oxidation began at approximately 259°C.…”
Section: Particles Characterizationsupporting
confidence: 81%
“…Grampone et al (2013) reported an oxidation temperature of 176°C using pure oxygen as oxidizing atmosphere at a higher rate.This could explain the diff erence, along with discrepancies in oil composition, as the omega-6 concentration is not reported by the authors. The same may be concluded when comparing to the results from Ixtaina et al (2012), who reported an oxidation temperature of (168.2 ± 2.8)°C. DSC thermograms demonstrated that the encapsulation of chia oil increased its oxidative stability since oxidation began at approximately 259°C.…”
Section: Particles Characterizationsupporting
confidence: 81%
“…Scientific literature has been reported researches related to the chia oil extraction (Ixtaina et al 2011a(Ixtaina et al , b, 2015Martínez et al 2012), its oxidative stability (Ixtaina et al 2012) and its potential use as vehicle to omega-3 FFA into foods Julio et al 2015;Rodea-González et al 2012). Furthermore, chia seed possess high levels of dietary fiber ([30 % of total weight) and a protein content in the range of 19-23 % (Sandoval-Oliveros and Paredes-López 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Se encontró 10,9% de ácidos grasos saturados y en ácido α-linolénico el resultado es semejante a los reportados por Martínez et al (2015) con 61,8%, Guiotto et al (2014) con 65,2% y por Ixtaina et al (2012) con 64,7%. El PV encontrado está dentro del límite permitido para aceites vírgenes y prensados en frío (PV ≤ 15 meq O2 / kg) (Codex Alimentarius, 2001).…”
Section: Resultados Y Discusiónunclassified
“…La exposición a EQ en animales y seres humanos a elevadas concentraciones debe ser evitada ya que tiende a acumularse en la corteza renal durante varios días después de una sola dosis; las lesiones renales inducidas por la administración crónica de una dieta que contiene EQ son zonas irregulares de la fibrosis, atrofia tubular, dilatación tubular focal, infiltración linfocítica, depósitos de material calcificado en el bulbo raquídeo y zonas de necrosis del tejido renal (Hernández et al, 1993 (Frankel, 2005;Lutterodt et al, 2010;Gharby et al, 2011;Krichene et al, 2010;García-Moreno et al, 2013;de Leonardis y Macciola, 2012); hasta el momento no se han publicado estudios de la influencia de diferentes temperaturas en la estabilidad oxidativa del aceite de chía con adición de antioxidantes y por consiguiente no se ha establecido su energía de activación. Estudios de aceite de chía con adición de antioxidantes sintéticos y naturales en rancimat han sido evaluados solo a temperatura de 100 °C por Bodoroina et al (2017) y a 98 °C por Ixtaina et al (2012). La temperatura representa un efecto estadísticamente significativo (p ≤ 0,05) sobre la determinación del OSI (García-Moreno et al, 2013), por ello este trabajo tuvo por objetivo determinar la influencia de los antioxidantes de origen natural y sintético a temperaturas de 90, 100 y 110 °C, así mismo estimar la influencia de los antioxidantes sobre la energía de activación de la reacción de autooxidación.…”
Section: O2unclassified
See 1 more Smart Citation